MATHEMATICAL MODEL OF MEMBRANE DISTILLATION PROCESS - Ladieva, L.; Dovbnya, S.; Dubik, R. (Science-based technologies, 2017)
The presented mathematical model of the process of membrane distillation, in which water vapor passes through the membrane and condenses on the surface, is cooled from the outside. This allows you to get clean water. The membrane module is considered as an object with lumped parameters, which consists of heat reservoirs: a solution channel, a clean water channel, and a cooling water channel. A mathematical model of technological contact membrane distillation is considered, taking into account the influence of the hydrodynamic flow of solution and distillate, the dimensions and characteristics of the membrane temperature conditions, with a specific mass flow of vapor through the membrane, thermal polarization on the productivity of the process, and nonlinear diffusion of vapors through the membrane. Static and transient characteristics are obtained. As a control, the costs for the cooling liquid are selected. As a controlled parameter, the drop in temperature of the solution and the distillate is selected, which drives the process.